What is the real impact of the change in the screening strategy for cervical cancer in Brazil? - Eleutério Junior, José; Passos, Mauro Romero Leal (Brazilian Journal of Sexually Transmitted Diseases, 2024)
n March 11, 2024, the Brazilian Ministry of Health approved the HPV-DNA test for cervical cancer screening through the National Commission for the Incorporation of Technologies in the Unified Health System (CONITEC). This development immediately raises several questions. What will the strategy be in Brazil when we transition to HPV DNA testing? Will there be a significant reduction in the number of cervical cancers? Undoubtedly, the challenge is substantial. There are many tests available. What will be the criteria for choosing the test? Which genotypes will be identified? Is it consistent with the local reality? In any case, new tools are always welcome and should be pursued. However, we must be careful not to create high expectations in a system before there is assurance and understanding that it will provide more significant and better benefits for the populations involved in the short and long-term.